3D bioprinting of in situ vascularized tissue engineered bone for repairing large segmental bone defects. (December 2022) - Shen, Mingkui; Wang, Lulu; Gao, Yi; Feng, Li; Xu, Chuangye; Li, Sijing; Wang, Xiaohu; Wu, Yulan; Guo, Yao; Pei, Guoxian
Abstract: Large bone defects remain an unsolved clinical challenge because of the lack of effective vascularization in newly formed bone tissue. 3D bioprinting is a fabrication technology with the potential to create vascularized bone grafts with biological activity for repairing bone defects. In this study, vascular endothelial cells laden with thermosensitive bio-ink were bioprinted in situ on the inner surfaces of interconnected tubular channels of bone mesenchymal stem cell-laden 3D-bioprinted scaffolds. Endothelial cells exhibited a more uniform distribution and greater seeding efficiency throughout the channels. In vitro, the in situ bioprinted endothelial cells can form a vascular network through proliferation and migration. The in situ vascularized tissue-engineered bone also resulted in a coupling effect between angiogenesis and osteogenesis. Moreover, RNA sequencing analysis revealed that the expression of genes related to osteogenesis and angiogenesis is upregulated in biological processes. The in vivo 3D-bioprinted in situ vascularized scaffolds exhibited excellent performance in promoting new bone formation in rat calvarial critical-sized defect models. Consequently, in situ vascularized tissue-engineered bones constructed using 3D bioprinting technology have a potential of being used as bone grafts for repairing large bone defects, with a possible clinical application in the future. Graphical abstract: Image 1 Highlights: 3D bioprinting was used to fabricate in situ vascularized tissue engineered bone. In situ bioprinted endothelial cells exhibited uniform distribution and greater seeding efficiency. 3D-bioprinted scaffold produced coupling between angiogenesis and osteogenesis.